Քթի խոռոչի լորձաթաղանթի վերականգնման պաթոգենետիկ մոտեցումները հետվիրահատական շրջանում - Նազանյան, Ա. Խ.; Մանասյան, Ս. Լ.; Պողոսյան, Ա. Կ.; Սարգսյան, Կ. Գ.; Շուքուրյան, Ա. Կ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В статье проанализированы особенности процессов восстановления слизи стой оболочки после операций на носу и околоносовых пазухах, с акцентом на роль трансформирующего фактора роста (TGF-β) и матриксных металлопротеиназ. Описаны основные проблемы тактики послеоперационного лечения, механизмы морфофункционального восстановления слизистой оболочки и факторы, вли яющие на них. Для эффективности восстановления подчёркнута важность сохране ния целостности мерцательного эпителия и контроля функции мукоцилиарной сис темы. Предложены перспективы развития исследований в этом направлении, ко торые могут способствовать совершенствованию реабилитационных мероприятий в ринологической практике. The article analyzes the characteristics of mucosal recovery processes after surgeries on the nose and paranasal sinuses, emphasizing the role of transforming growth factor (TGF-β) and matrix metalloproteinases. The main challenges of postoperative treatment strategies, mechanisms of morphofunctional recovery of the mucosa, and influencing factors are described. The importance of preserving the integrity of the ciliated epithelium and controlling the function of the mucociliary system is highlighted for effective recovery. Prospects for further research in this area, which may contribute to the improvement of rehabilitation measures in rhinological practice, are proposed.
Keywords: Ռինոլոգիական վիրահատություններ